Prognostic significance of CD204 and IDO1 expression in esophageal tumors - O. V. Kovaleva; O. V. Rashidova; V. V. Mochalnikova; D. V. Samoilova; P. A. Podlesnaya; A. N. Gratchev (Успехи молекулярной онкологии, 2021)
Introduction. Cancer of the esophagus ranks sixth in mortality among malignant neoplastic diseases. To understand the molecular mechanisms of its progression, it is necessary to study not only tumor cells directly, but also cells of the microenvironment. In this work, we studied tumor-associated macrophages and their different phenotypes using membrane protein, indoleamine 2,3‑dioxygenase-1 (IDO1) as a marker for type 1 macrophages and macrophage scavenger receptor (CD204) as a marker for type 2 macrophages.The objective of this work was to study the expression of IDO1 and CD204 in tumors of squamous cell carcinoma of the esophagus and to assess its prognostic value.Materials and methods. The study included tumor samples obtained from 48 patients with squamous cell carcinoma of the esophagus. The expression of CD204 and IDO1 was assessed by immunohistochemistry. Survival analysis was carried out by constructing survival curves using the Kaplan–Meier method. Comparison of the significance of differences was performed using the logarithmic rank test. Differences were considered statistically significant at p <0.05.Results. We analyzed the expression of CD204 and IDO1 in esophageal squamous cell carcinoma tumors. Expression of CD204 was detected in stromal macrophages in 100 % of cases and was not detected in tumor cells. We have shown that in esophageal cancer, IDO1 is expressed in both stromal and tumor cells. In tumor cells, the expression of IDO1 was found in 44 % of the samples, in stromal cells, IDO1 was expressed in 92 % of cases. No association with clinical and morphological characteristics was observed for CD204 in stromal cells and IDO1 in tumor cells. For IDO1 expressed in stromal cells, an association with the stage of the disease (p = 0.0450) and the presence of regional metastases (p = 0.0279) was observed. Survival analysis showed that CD204 is a marker of a favorable prognosis for esophageal cancer (hazard ratio 0.455, p = 0.0419).Conclusion. This study has shown that the expression of IDO1 in the tumor stroma is associated with more favorable clinical characteristics. It has also been shown that an increased content of CD204+ macrophages is a marker of a good prognosis for esophageal cancer.